The People's Republic of China's high-tech exports: Myth and reality - Yuqing Xing (Asian Development Bank Institute (ADBI), 2012)
Trade statistics portray the People's Republic of China (PRC) as the largest exporter of high-tech products. In this paper I will argue that the PRC's leading position in high-tech exports is a myth created by outdated trade statistics which are inconsistent with trade based on global supply chains. Current trade statistics mistakenly credit entire values of assembled high-tech products to the PRC, thus greatly inflating its exports. In 2009, the PRC's value-added accounted for only about 3% of the total value attributed to its exports of iPhones and laptop personal computers. Moreover, 82% of the PRC's high-tech exports were produced by foreign-invested firms, in particular Taipei,China-owned companies. In this paper I will argue that a value-added-based approach should be adopted to accurately measure high-tech exports. Furthermore, if assembly is the only source of the value-added generated by PRC workers, in terms of technological contribution these assembled high-tech exports are no different from labor-intensive products, and so they should be excluded from the high-tech classification.
Keywords: F1; F2; 330; prc; high-tech; value added; iphone; Hochtechnologie; Export; Vorleistungen; China